2013
DOI: 10.1021/ma302567j
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Probe Molecule Dissolved in Several Polymer Matrices with Different Side-Chain Structures: Determination of Correlation Length Relevant to Glass Transition

Abstract: Dynamics of 4-pentyl-4′-cyanobiphenyl (5CB) dissolved in several polymers at concentrations of 3−7 wt % was examined by dielectric relaxation measurement. Glassy (segmental) mode of the matrix polymer was also investigated by viscoelastic measurements for the same samples. Polystyrene (PS), poly(4-methylstyrene) (P4MS), and poly(4-tertbutylstyrene) (PtBS) were used as host polymers, considering that they have the same backbone structure but different sidechain bulkiness. Two dielectric relaxation modes (slow a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
2
7
0
Order By: Relevance
“…51,59 These segment sizes could be associated with Kuhn's segment length. 124 This assumption is in agreement with the work of Shogo et al, 119 showing that the cooperative motion in stiff backbone polymers may be correlated to Kuhn's segment length.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…51,59 These segment sizes could be associated with Kuhn's segment length. 124 This assumption is in agreement with the work of Shogo et al, 119 showing that the cooperative motion in stiff backbone polymers may be correlated to Kuhn's segment length.…”
Section: ■ Results and Discussionsupporting
confidence: 90%
“…In fact, it can be found that for more rigid backbone polymers, cooperative motions involve some statistical segments of the macromolecule rather than the whole repeating units. , These segment sizes could be associated with Kuhn’s segment length . This assumption is in agreement with the work of Shogo et al, showing that the cooperative motion in stiff backbone polymers may be correlated to Kuhn’s segment length.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…According to the MD simulation [ 19 ], the increase of the LiTFSI concentration leads to the formation of some Li–TFSI coordinated species free from the polymer backbone, such as Li(TFSI) 3 , in addition to free TFSI anions. These species may work as plasticizers of the polymer component, i.e., behave as dynamically fast components, resulting in the dynamically heterogeneous behaviors, such as the broadening of the G * and tan δ spectral shapes and the appearance of prominent fast component dynamics in the high ω region [ 43 , 44 , 45 , 46 ]. Specifically, by looking at the high-frequency region of ω > 10 6 s −1 for the = 0.25 and 0.30 data, the slopes of tan δ (and G ″) are weaker than those at smaller , suggesting the existence of the fast relaxation component in the viscoelastic spectra.…”
Section: Resultsmentioning
confidence: 99%
“…With addition of p ‐tPh, the α peaks in E ″ and O ″ shift to lower temperature but the peak strength in O ″ slightly increases. We previously reported that a small molecule exhibits a cooperative glass transition with a matrix polymer when the molecular size is consistent with the chain segment . Because p ‐tPh has large polarizability anisotropy originating from the three phenyl groups, the increase of the O ″ peak intensity suggests that p ‐tPh also contributes to the increase of the α peak with increasing p ‐tPh content.…”
Section: Resultsmentioning
confidence: 99%